Effectiveness of remdesivir for hospitalized COVID-19 patients depending on the severity of respiratory status: a multicenter retrospective study in Japan - Hidero Yoshimoto; Kazuma Yamakawa; Yoshihiro Tanaka; Itsuki Osawa; Takashi Tagami; Akira Endo; Ryo Yamamoto; Mineji Hayakawa; Takayuki Ogura; Atsushi Hirayama; Hideo Yasunaga; Akira Takasu; et al. (BMC Infectious Diseases)
Abstract Background Remdesivir, an antiviral nucleotide analog prodrug, is approved for clinical use against COVID-19 worldwide. However, its effectiveness varies depending on the respiratory failure status of patients. This study aimed to evaluate the effectiveness of remdesivir treatment based on the severity of respiratory failure, as indicated by the oxygen demand upon hospital admission. Subgroups analyses were conducted to identify patient groups that might benefit from remdesivir treatment. Methods This retrospective observational study (the J-RECOVER) enrolled patients with COVID-19 from 64 institutions in Japan between January 1 and September 30, 2020. Patients aged ≥ 18 years who were administered remdesivir within 3 days of hospital admission were included. A total of 3,591 patients were included, and propensity score overlap weighting analysis was used to compare in-hospital mortality based on respiratory failure status at admission between remdesivir and control groups. Subgroup analyses identified specific patient populations that may benefit most from remdesivir treatment, considering factors such as respiratory status and renal function. Results The overlap weighting (OW)-adjusted odds ratio (OR) for mortality in overall cohort, mild cases without supplemental oxygen, moderate cases requiring supplemental oxygen, and severe cases requiring ventilation was (OR, 0.65 (95% confidence interval (CI), 0.36–1.19; P = 0.16), 0.11 (95% CI, 0.01–1.03; P = 0.05). 0.82 (95% CI, 0.31–2.16; P = 0.69), and 0.78 (95% CI, 0.28–2.17; P = 0.63), respectively. A trend toward improvement in mortality was observed in respiratory indicators, such as SpO2 ≥ 94% (OR, 0.43; 95% CI, 0.19–0.99; P = 0.04), oxygen support with FiO2 < 0.5 (OR, 0.40; 95% CI, 0.16–0.97; P = 0.04), and PFR ≥ 300 (OR, 0.17; 95% CI, 0.03–0.94; P = 0.04). Subgroup analyses indicated improved mortality in patients with an estimated glomerular filtration rate (eGFR) of > 60 mL/min per 1.73 m2 (OR, 0.29; 95% CI, 0.09–0.94; P = 0.03), with a p-value for interaction of P = 0.18. Conclusion Remdesivir treatment may reduce the risk of in-hospital mortality in patients with mild respiratory distress. Subgroup analysis suggested that remdesivir treatment may improve mortality in patients with eGFR ≥ 60 mL/min per 1.73 m2.